Improved Cloud Storage System Using IPFS for Decentralised Data Storage - Kumar, Pratham; Gupta, Meenu; Kumar, Rakesh (2023 International Conference on Data Science and Network Security (ICDSNS), 2023)
Cloud storage is widely used for storing and accessing data, but centralized storage solutions can be vulnerable to security breaches. Decentralised data storage solutions offer an alternative approach that mitigates these risks by distributing data across a network. The Interplanetary File System (IPFS) is a peer-to-peer protocol that provides a decentralised storage solution for data. In this paper, we propose an improved cloud storage system using IPFS for decentralised data storage. The proposed system provides a secure and flexible solution to cloud storage that can be customized and extended to meet specific needs. The system utilizes IPFS technology to create a decentralised and secure storage solution for data and incorporates features such as redundancy and encryption to enhance data protection. The system provides a secure and distributed approach to data storage that mitigates the risks associated with centralized storage solutions. The research outcomes demonstrate that the improved cloud storage system, which utilizes IPFS for decentralised data storage, offers notable benefits. By distributing data across nodes, it minimizes the risk of singlepoint failures and enhances data availability. The system's redundancy mechanisms improve fault tolerance and reliability. Data security is reinforced through the integration of encryption techniques, safeguarding sensitive information. The evaluation reveals competitive performance metrics, with retrieval times and latency that are comparable to or surpass existing cloud storage solutions. In summary, the enhanced IPFS-based system provides a viable alternative for decentralised data storage needs, offering improved security, scalability, and performance.